(NmUZYKAs (NKNIGA DLQ ^ETWERTOGO KLASSA(B.s - (Nm(B.(NrUMER(B.s; (Ne(B.(NdOMRINA(B.s (NDRUGOJ AWTORs; (Nn(B.(NkULIKOWA(B.s (NDRUGOJ AWTORs ((NmOSKWAs (NmUZYKAs, 1978)
(NuZNATX NOWOEO MUZYKE WAM POXOVET \TA KNIGA(B.s
Keywords: (NmUZYKALXNOE OBROZAWANIEs